PENGARUH PELAPISAN CHITOSAN TERHADAP DAYA SIMPAN BUAH MANGGA (Mangifera indica L.) - Paulya Eltje Leihitu; Gilang Andi Nugroho; Bellarose Novelia Pandeirot; Brian Jordan Zendrato; Peli Rodo; Chelsy Natalia Putirulan; Erlitha Rahmawati; Velian Sandy Wardana; Teresha Elena Permata; Yoga Aji Handoko; Vania Putri Santoso (Universitas Muhammadiyah Purwokerto, 2021)
Mango (Mangifera indica L.) is a climacteric fruit, which is able to continue the process of ripening after harvest. The mangoes that have been harvested experience a spike in the respiration rate, which can reduce the shelf life of the fruit. Thus, efforts are needed to reduce the rate of fruit respiration. One method that can be used to reduce the respiration rate of fruit is chitosan coating. The purpose of this study was to determine the effect of the concentration of chitosan solution on the shelf life of mangoes. This research was conducted at the Postharvest Handling Laboratory, Faculty of Agriculture and Business, Satya Wacana Christian University. This study uses two types of mangoes, namely arum manis and kweni mangoes with three treatments, namely control, chitosan concentration of 1% and chitosan concentration of 2%. The results of this study are the coating of fruit with chitosan affects the rate of respiration, moisture content, and weight loss. Chitosan 1% treatment can suppress the respiration rate of sweet arum mango 0.034 CO2 /g/minute and 0.022 CO2 /g/minute on kweni mangoes. Chitosan 1% treatment can reduce the weight loss in sweet arum 6.15% and 11.33% in kweni mango. Chitosan 2% treatment can hold the water content in kweni mangoes up to 9.01%.